Immediate and Short-Term Variations in the Echocardiographic Cardiac Hemodynamic Parameters after the Transcatheter Atrial Septal Defect Device Closure and its Procedural Success. - Yadav, Vijay; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Khanal, Rajaram; Shakya, Smriti; Sharma, Manju; Adhikari, Suman; Sahi, Ravi (Nepalese Heart Journal, 2022)
Background and Aims:Transcatheter closure of the secundum atrial septal defect (ASD) has become an accepted alternative to surgical repair. We aimed to analyze and compare the changes in cardiac hemodynamics with transthoracic echocardiography (TTE) before, within 48 hours, and after 3 months of ASD closure. Methods: This was a prospective, single-centered study of 43 patients who underwent ASD device closure in the Manmohan Cardiothoracic Vascular and Transplant Center during June 2020 to June 2021 with Amplatzer Septal Occluder under transesophageal and fluoroscopic guidance. The patients were evaluated with TTE before, at 48 hours, and 3 months after the procedure. Results: At 48 hours and 3 months of device closure, the right atrial major dimension, the maximum blood flow velocity at the pulmonary valve orifice, mean flow velocity, velocity time integral, and E peak and A peak blood flow velocity at the tricuspid valve orifice were significantly reduced (P < 0.001). At 3 months, the dimensions and ejection fraction of the left ventricle showed significant increment (P < 0.001). Likewise, the right atrial minor dimension and area, right ventricular basal, mid, and longitudinal dimensions, tricuspid annular plane systolic excursion, right ventricular Tei Index, and fractional area change were significantly reduced (P < 0.001). The main pulmonary artery diameter, pulmonary artery systolic and mean pressure, and the pulmonary vascular resistance and index were significantly reduced (p <0.001). The procedural success rate was 97.6%. Conclusion: Echocardiographic evaluation demonstrated that cardiac hemodynamics and loading conditions improved significantly at 3 months after percutaneous closure of ASD. The transcatheter closure of ASD was safe with good short-term outcomes.